Pembuatan Game Edukasi Bahasa Inggris Untuk Meningkatkan Kosakata Bagi Peserta Tidar - Farhan Hanif, Muhammad; Andriyanto, Sidhiq; Mubaroh, Sari (Jurnal Inovasi Teknologi Terapan, 2024)
Technology is growing rapidly and has affected many aspects of life today. Technology is being used more and more frequently and the most utilized language is English. Tidar English Course provides tutoring for English, but Tidar 7th and 8th grade participants have difficulty in learning and memorizing English vocabulary. To overcome these problems, an application is made to help Tidar 7th and 8th-grade participants learn vocabulary with educational game media. Learning will be packaged into a crossword puzzle game so that it can train their vocabulary by finding the right answer in the crossword puzzle boxes that have been provided. The development method in this research is using Game Development Life Cycle (GDLC), and the testing method uses the User Acceptance Test (UAT). The system testing in this study uses black box testing. User Acceptance Test (UAT) testing submitted to the teacher gets 100% of Tidar 82.44% for grade 7 Tidar participants and 84.22% for grade 8 Tidar participants. It can be concluded that the results of the three User Acceptance Tests (UAT) get the criteria "Very Feasible"